2014
DOI: 10.1136/bcr-2013-203281
|View full text |Cite
|
Sign up to set email alerts
|

Adult intussusception presenting as rectal prolapse

Abstract: We present a case of an elderly man with what appeared to be an episode of rectal prolapse following straining while defaecating. Laparotomy revealed the prolapse to be an intussusception of large bowel with a villous adenoma as its lead point. Reduction resection was performed with primary anastomosis, and the patient recovered well from the surgery. Rectal prolapse has often been viewed as a benign condition in the elderly, but more thought needs to be put into the diagnosis in patients with risks of maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Most reports state that 70%–90% of cases have an identifiable source, a lead point, with 40%–50% being due to a malignancy and only 10% being idiopathic 4. There are published case reports discussing sigmoid intussuception through the rectum due to lipoma or malignancy 5–13. Our case report adds to the current literature by reporting on two cases that were idiopathic in nature without lead point/malignancy.…”
Section: Discussionmentioning
confidence: 62%
“…Most reports state that 70%–90% of cases have an identifiable source, a lead point, with 40%–50% being due to a malignancy and only 10% being idiopathic 4. There are published case reports discussing sigmoid intussuception through the rectum due to lipoma or malignancy 5–13. Our case report adds to the current literature by reporting on two cases that were idiopathic in nature without lead point/malignancy.…”
Section: Discussionmentioning
confidence: 62%
“…Pre-operative colonoscopies and imaging can limit the need for a colon resection with identification of benign lesions [ 8 ]. It can however be difficult to diagnose these pre-operatively [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…After assessing patient's hemodynamic status, a contrast enhanced abdomino-pelvic CT scan should be performed to investigate potential conditions associated with complicated RP [213][214][215][216], such as acute bowel obstruction, signs of perforation and peritonitis, prolapse of other pelvic organs (uterus, vagina and/or bladder, sigmoid colon, small bowel) [217], and to rule out the presence of colorectal malignancy. A sudden RP could be the first clinical manifestation of a colon cancer, as demonstrated by several case reports [218][219][220][221]; therefore, multiple authors suggest that patients with rectal prolapse should have endoscopic examination of the colon and rectum. Akyuz et al hypothesized that the age group in which RP is most commonly seen, the change in bowel habits, the chronic constipation, and mucosal irritation related to this disease, could be the factors that increase the incidence of rectum cancer in patients with RP and concluded that endoscopic screening should not be overlooked in this specific population [222].…”
Section: B -In Patients With a Suspected Complicated Rectal Prolapse Which Are The Appropriate Imaging Investigations?mentioning
confidence: 99%